2021
DOI: 10.1186/s12877-021-02381-w
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and barriers: a qualitative study on online social participation among widowed older adults in Southwest China

Abstract: Background With the development of digital media, online activities are increasingly becoming part of the daily life of older adults. Widowed older adults generally would face changes in social interactions and activities due to widowhood; thus, the importance of online participation may be more prominent in this population. However, a detailed evidence on the experiences of online social participation among widowed older adults is relatively sparse. This study aimed to explore widowed older ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
(42 reference statements)
1
4
0
1
Order By: Relevance
“…Psychologically, despite the elders living alone often feeling lonely, there is a lack of community attention to their mental health, which is often overshadowed by physical health (56). Our interview coincides with previous studies that online social interaction with peers plays an essential role in the interpersonal relationships of older adults living alone, increasing their social involvement and enhancing their sense of happiness (57,58).…”
Section: Discussionsupporting
confidence: 79%
“…Psychologically, despite the elders living alone often feeling lonely, there is a lack of community attention to their mental health, which is often overshadowed by physical health (56). Our interview coincides with previous studies that online social interaction with peers plays an essential role in the interpersonal relationships of older adults living alone, increasing their social involvement and enhancing their sense of happiness (57,58).…”
Section: Discussionsupporting
confidence: 79%
“…Finally, age and widowed marital status are hindering factors for Internet and HIT use. On the one hand, some surveys showed that older adults usually have some degree of cybersecurity concerns and digital skills anxiety [33], further limiting their acceptance and use of new technologies such as the Internet in their sickly physical condition, and on the other hand, widowhood deepens older adults' sense of isolation [34], which may also be detrimental to enhancing their acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the older generation in China can communicate with the outside world through mobile phones and the Internet, which may reduce the intimate association between leisure, entertainment, and social health. Therefore, the LEL of older people living alone may increase the possibility of social interaction, but there are still challenges in prompting them to actively improve their social health premised on social trust or social reciprocity in a short period ( 85 ).…”
Section: Discussionmentioning
confidence: 99%